Integrating robotic surgery and pharmacotherapy: A dual approach to lung cancer management - Gnanendra Sai Kumar Nareboina; Prudhvi Raj Chalapaka (Intelligent Surgery)
Medication and robotic surgery are new approaches in the treatment of lung cancer. To obtain the goal of radical surgical treatment of the tumor, this effective approach takes advantage of the accuracy of robotic surgical system in combination with the pharmacological strategies that are aimed at achieving the highest therapeutic intervention and the minimal toxic effects.Patient selection and survival data are required for desired long-term effects. The success of this method depends on training and learning curves for health care providers. Clinical applications emphasize the necessity of robotic assisted strategies and efficient use of consumables and advanced robotic bronchoscopy. This innovative approach helps to improve the lung cancer treatment by setting a new standard for patient outcomes.